Determinants of voluntary IFRS adoption in an emerging market: Evidence from Turkey - Yigit Bora Senyigi (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The European Commission has required the adoption of IFRS in order to harmonize financial reporting standards for European listed companies as of 1 January 2005. Adoption of IFRS by European Union has made IFRS the most widely accepted financial reporting standards in the world. Turkey, having close economic and political ties with the European Union, has followed the same path. Turkish firms listed on the Borsa Istanbul (stock exchange of Turkey) started to adopt financial reporting standards in compliance with IFRS voluntarily in 2003 and mandatorily in 2005. This study aims to examine empirically the determinants of voluntary IFRS adoption of listed firms in Turkey. This study reports on the results of an empirical investigation of the determinants of voluntary IFRS adoption by 206 non-financial firms listed on the Borsa Istanbul. Analyzing the determinants of voluntary IFRS adoption by Turkish listed firms during the transition period, we find that size, international exposure, and type of auditor are important drivers
Keywords: M41; 650; IFRS; voluntary adoption; emerging market; Turkey